Evaluation of Self-Care and its Association with Quality of Life in Patients with Type 2 Diabetes - Masoumeh Gholizadeh; Somayeh Heydari; Nazanin Mir; Havjin Taghipour; Nasser Hatamzadeh; Habib Jalilian (Shahid Sadoughi University of Medical Sciences, 2022)
Background: Diabetes is a chronic illness which requires continuous self-care. Appropriate self-care can reduce the risks of developing complications and improve the Quality of Life (QoL). This study aimed to examine self-care and its association with quality of life in patients with type 2 diabetes (T2DM) in East Azerbaijan, Iran, in 2018. Methods: This was a cross-sectional study. The statistical population included all patients with type 2 diabetes in East Azerbaijan, in 2018. 310 patients were included using consecutive sampling. The summary of Diabetes Self-Care Activities  Questionnaire (SDSCA) and the 12-Item Short Form Health Survey questionnaire (SF-12) were used for data collection. Data were analyzed using SPSS22.  Descriptive statistics such as mean, Standard Deviation (SD), frequency, and percentage were applied to describe the characteristics of the respondents. The Spearman correlation, Mann Whitney U and Kruskal-Wallis tests were applied for statistical analysis. Results: The mean scores of self-care and QoL were estimated to be 42.14 ± 61.63 and 53.25 ± 51.73, respectively. The highest mean of self-care and QoL was related to medications and social functioning which were 96.03 and 68.34. There was no correlation between the total mean score of self-care and QoL (P-value = 0.65). Moreover, a significant correlation was found between medication (insulin), exercise, blood-glucose testing and the total score of QoL (P-value < 0 .05). Conclusion: The results indicated that self-care in patients with diabetes is poor, and the patients' QoL is moderate. Therefore, it is suggested that managers of health centres take appropriate measures such as educational programs and executive interventions to enhance self-care in patients with diabetes. Moreover, to increase QoL, more attention should be paid to promote exercise and diet behaviours.